2006
DOI: 10.1007/s10584-006-9050-5
|View full text |Cite
|
Sign up to set email alerts
|

Do Regional Disparities in Research on Climate and Water Influence Adaptive Capacity?

Abstract: Abstract. As part of a long-term effort to both improve access to information on climate change and freshwater resources, and to understand the state of the science, we compiled an electronic bibliography of scientific literature in that area. We analyzed the distribution of information on climatic impacts on freshwater resources, with an emphasis on differences between developed and developing regions as well as differences in the types and focus of research carried out among regions. There has been more rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…As noticed for other clusters, some of the high-ranking words did not provide real information (i.e., "land", "region"), and so a further analysis was performed to highlight which countries have been objective of scientific research. When focusing on top ranking countries, research was mainly biased toward largest and richest nations (United States 19.2%, United Kingdom 7.5%, Australia 6.7%) which are the less vulnerable [36][37][38]. Nevertheless, going through the list, it is noticeable that a substantial number of documents deal with developing countries (China 6.9%, India 5.9%, Viet Nam 0.7%).…”
Section: Class 22: Cluster Analysismentioning
confidence: 99%
“…As noticed for other clusters, some of the high-ranking words did not provide real information (i.e., "land", "region"), and so a further analysis was performed to highlight which countries have been objective of scientific research. When focusing on top ranking countries, research was mainly biased toward largest and richest nations (United States 19.2%, United Kingdom 7.5%, Australia 6.7%) which are the less vulnerable [36][37][38]. Nevertheless, going through the list, it is noticeable that a substantial number of documents deal with developing countries (China 6.9%, India 5.9%, Viet Nam 0.7%).…”
Section: Class 22: Cluster Analysismentioning
confidence: 99%
“…Participant observation during management and policy meetings and semi-structured interviews (Spradley, 1979) with scientists and decision makers involved in California water management complimented publicly available data. Informants involved with the issue of climate change were identified through previous research in a larger study of climate change science and California water management, including a scientific literature review (Kiparsky & Gleick, 2003), a comprehensive bibliography of water-related climate science (Kiparsky et al, 2006), an analysis of policy recommendations by scientists (Kiparsky & Gleick, 2005) and a historical review of scientific milestones (Kiparsky, 2004). All respondents remain anonymous, in accordance with guidelines of U.C.…”
Section: Methodsmentioning
confidence: 99%
“…For the top 20 most productive countries (based on institutional affiliation of the first authors) for climate change research only includes one African country (South Africa, 16th) and no major African countries when population size is factored in. Similarly, Kiparsky et al [27] found that climate change research tended to focus heavily on North America, Global and European geographies, with Africa and Asia following. In their analysis of the Intergovernmental Panel on Climate Change (IPCC) reports Ho-Lem et al [28] suggest that only 4% of the authors were African and when population was considered were the second most underrepresent geography by continent after Asia.…”
Section: Knowledge Systems For Governance Of Inclusive Green Growth Imentioning
confidence: 99%